2016
DOI: 10.1093/jee/tow079
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity and Nonrepellency of Spinosad and Spinetoram on Formosan Subterranean Termites (Isoptera: Rhinotermitidae)

Abstract: Spinosyn products, spinosad and spinetoram, are widely used to control various agricultural pests. Spinosad has been tested on Kalotermitidae and Termitidae but not on Rhinotermitidae, the most destructive of termite families. In this study, we tested the effect of spinosad and spinetoram on Coptotermes formosanus Shiraki. Both no-choice and choice tests were conducted using three concentrations, 1 ppm, 25 ppm, and 50 ppm, of the spinosyn products Entrust, Tracer, and Radiant on three substrates, sand, soil, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Results show that spinetoram is more toxic to R. indifferens than spinosad, as measured by fly kill using the protocol here, and that all age groups of flies are similarly affected. Spinetoram is also more toxic than spinosad against many insects (Dripps et al 2008a,b; Abdel-Latif and Abdu-Allah 2011; Hamm et al 2015; Siebert et al 2016; Andreazza et al 2017), but possibly not against all (Besard et al 2011, Athanassiou and Kavallieratos 2014, Bhatta et al 2016), including fruit flies (Schutze et al 2018). For nontarget insects, whether spinetoram is more toxic than spinosad appears to depend on the insect taxa (Lefkaditis et al 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results show that spinetoram is more toxic to R. indifferens than spinosad, as measured by fly kill using the protocol here, and that all age groups of flies are similarly affected. Spinetoram is also more toxic than spinosad against many insects (Dripps et al 2008a,b; Abdel-Latif and Abdu-Allah 2011; Hamm et al 2015; Siebert et al 2016; Andreazza et al 2017), but possibly not against all (Besard et al 2011, Athanassiou and Kavallieratos 2014, Bhatta et al 2016), including fruit flies (Schutze et al 2018). For nontarget insects, whether spinetoram is more toxic than spinosad appears to depend on the insect taxa (Lefkaditis et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Work comparing spinosad with spinetoram against a wide range of insect taxa has recently been published (e.g., Abdel-Latif and Abdu-Allah 2011, Besard et al 2011, Hamm et al 2015, Bhatta et al 2016, Siebert et al 2016, Andreazza et al 2017). However, little work in this area has been done for tephritid fruit flies.…”
mentioning
confidence: 99%
“…Bhatta et al . (2016) tested the toxicity and repellency of spinosad and spinetoram against Coptotermes formosanus under laboratory conditions and reported that both insecticides exhibited toxicity and non‐repellency against termites. Huang et al .…”
Section: Chemical Control Measuresmentioning
confidence: 99%
“…In addition, a few studies were done to determine the efficiency of spinosad on subterranean termites (eg. Scheffrahn et al, 1997;Scheffrahn and Thoms 1999;Iqbal and Saeed 2013;Bhatta et al, 2016).…”
Section: Introductionmentioning
confidence: 99%